Mudanças tecnológicas no setor agroalimentar ibérico: possibilidades de inovação inclusiva e desenvolvimento territorial - Tartaruga, Iván Gerardo Peyré (2022)
Nowadays, the world is going through an accelerated period of great technological transformations that can be exemplified by advances in digitalization (big data, artificial intelligence and automation), nanotechnology, biotechnology, genetics, etc. Therefore, the growing attention of academia and governments in theoretical perspectives, such as Technological Revolutions or Deep Transitions (sociotechnical), to understand these changes that affect all economies and societies. In this context, the very notion of territorial development must change in order to encompass new dimensions, in addition to the traditional ones (social well-being, economic competitiveness and social cohesion), such as environmental sustainability (sustainable development) and technological appropriation (technological development). Specifically, the agri-food sector is also influenced by these transformations in various activities: in the big data services related to agriculture offered by Microsoft, Google and IBM; or wholesale food trade by Amazon and Alibaba. Although important for the economy of the Iberian Peninsula, this sector has weaknesses, mainly in terms of technology and economic exclusion of part of the population. For this reason, the relevance of the approach to inclusive innovations seems evident, that is, those innovations (product or production process) aimed at strata of the low-income population or even developed by these people. The objective of this research is to establish an agro-food economic geography for Spain and Portugal, revealing the potential of inclusive innovation for territorial development and considering urban-rural relations as essential in the exchange of knowledge (analytical, synthetic and symbolic). Methodologically, the study is based on indicators and experiences linked to the European Smart Specialization and Horizon 2020 programs. In conclusion, there is potential for development, especially in the links between universities and rural actors aimed at inclusion and sustainability, highlighting the need for reconfiguration of agri-food systems and integration into global value chains.